Agrotechnical and economical alternatives for pea culture in Turda area - Alina Şimon; Teodor Rusu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The aims of this experiment are to evaluate the yield of pea cultivated in conventional and reduced tillage and the economy of minimum tillage systems application. Soil is the primary factor determining the plants yield of a particular area. Yield of pea is determined by multiple factors and the yield variability may be difficult to predict. The experimental factors are: factor A-the experimental years 2014 and 2015, factor B-three tillage systems: conventional, minimum and no tillage. In 2014 was obtained a higher production than in 2015, with a very significant difference. Pea production decreases after applying conservative systems, with 204 kg/ha in minimum system and 611 kg/ha in no tillage system. Fuel consumption used for to perform basic works is higher in the variant to which the soil is plowed compared with minimum tillage systems. The highest costs in achieving the yield/1 ha are recorded in the classical tillage variant, with 12.78% respectively 19.31% higher than in minimum tillage systems. Seedbed preparation is the element of the culture technology where by applying minimum tillage systems can reduce the cost, in no tillage system this technological stage being eliminated.
Keywords: Q01; Q15; Q16; 330; climatic condition; economy; pea; tillage systems; yield